2020
DOI: 10.1094/pdis-05-20-0994-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Colletotrichum Leaf Spot of Macadamia Caused by Colletotrichum siamense in China

Abstract: Macadamia (Macadamia integrifolia Maiden & Betche), growing in tropical and subtropical regions worldwide, is a high-value tree nut (Akinsanmi and Drenth 2017). In May 2018, the leaves of macadamia trees showed symptoms of anthracnose, with an incidence 10-15%, in Chongzuo (22°32′ N; 107°38′ E) (Guangxi province) in China. The disease begin to develop from the tip of leaf or the margin of leaf. Initially, the disease symptoms on leaves were water-soaked, black grey, light-yellow around, which enlarged and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…In China, various diseases caused by C. siamense can infect other hosts include Sterculia nobilis (Zhang et al 2020a, b), Sterculia lanceolata (Zhang et al 2020a, b), Hevea brasiliensis (rubber tree) (Cao et al 2019), Mallotus oblongifolius (Partridge tea) (Liu et al 2018), Macadamia sp. (Qiu et al 2020), Litchi chinensis (Ling et al 2019), and Camellia sinensis (Wang et al 2016). Although there have been other reports of Colletotrichum species on S. tonkinensis, namely C. gloeosporioides (Shivas and Alcorn 1996) and C. simmondsii (as an endophyte from roots) (Yao et al 2017), ours is the first known record of C. siamense on the plant of S. tonkinensis.…”
mentioning
confidence: 71%
“…In China, various diseases caused by C. siamense can infect other hosts include Sterculia nobilis (Zhang et al 2020a, b), Sterculia lanceolata (Zhang et al 2020a, b), Hevea brasiliensis (rubber tree) (Cao et al 2019), Mallotus oblongifolius (Partridge tea) (Liu et al 2018), Macadamia sp. (Qiu et al 2020), Litchi chinensis (Ling et al 2019), and Camellia sinensis (Wang et al 2016). Although there have been other reports of Colletotrichum species on S. tonkinensis, namely C. gloeosporioides (Shivas and Alcorn 1996) and C. simmondsii (as an endophyte from roots) (Yao et al 2017), ours is the first known record of C. siamense on the plant of S. tonkinensis.…”
mentioning
confidence: 71%
“…It can infect many plants and cause many diseases (Weir et al, 2012), such as crown rot in strawberries (Luo et al, 2021), as well as anthracnose disease and leaf disease in many plants, including Citrus spp., Piper nigrum, Artocarpus heterophyllus, Artocarpus sericicarpus, Coffea arabica, Coffea canephora, Eriobotrya japonica, Ficus carica, Mentha sp., Rosmarinus officinalis, Theobroma cacao, Jasminum sambac, Pongamia pinnata, Bauhinia forficata subsp. pruinose and Macadamia integrifolia, (Wikee et al, 2011;James et al, 2014;Larran et al, 2015;Dwarka et al, 2016;Qiu et al, 2020;Jian et al, 2021;Perez-Mora et al, 2021;Wang et al, 2021). Casas et al (2021a, b) reported that C. siamense can be endophytic and is used as a biological control in anthracnose disease.…”
Section: Discussionmentioning
confidence: 99%
“…As such it can cause preharvest fruit anthracnose in Carica papaya L. [40], Litchi chinensis [18,41], Acca sellowiana [42], Fragaria ananassa Duch [43], Citrus spp. [44], Walnut (Juglans regia L.) [14], postharvest fruit anthracnose in Mangifera indica [45], crown rot and anthracnose in roots, runner of Fragaria ananassa Duch [43], leaf spot in rubber (Hevea brasiliensis) [37], Thai basil (Ocimum basilicum) [46], and Macadamia (Macadamia integrifolia) [27,30]. Recently Kumar et al [47] and Salunkhe et al [48] also reported C. siamense as the causal organism of Cliff Banana and cotton anthracnose in the neighboring country India.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the distinct leaf blight/spot symptom was also consistent with Colletotrichum Leaf Spot of Macadamia and Chrysalidocarpus lutescens (areca palm). In these hosts, the disease began to develop from the lea tip or the leaf margin as small spots, followed by coalescing into a large spot, then ending in necrosis and defoliation in severe cases [27, 28]. To the author's knowledge, no such symptoms (as described above) were reported for the C. tamala plant in Bangladesh or even in other countries.…”
Section: Discussionmentioning
confidence: 99%